Pemanfaatan Media Pembelajaran Berbasis Augmented Reality (AR) untuk Meningkatkan Literasi Sains Siswa Sekolah Dasar di Daerah 3T Kabupaten Sabu Raijua, Nusa Tenggara Timur - Fathan Zarkasi; Maya Fitria (Lembaga Publikasi Ilmiah Nusantara, 2026)
The execution of this community service activity was based on the low science literacy among elementary school students in Frontier, Outermost, and Underdeveloped (3T) regions, particularly in Sabu Raijua Regency, East Nusa Tenggara. The limited availability of visual learning aids makes abstract science concepts difficult to comprehend. This activity aimed to enhance the science literacy of elementary school students by utilizing Augmented Reality (AR)-based learning media that is interactive and adaptive to local conditions. Method: The method applied in this service program involved structured training and mentoring (action research). The target participants included elementary school teachers and students in the partner region. Implementation stages consisted of an AR technology introduction workshop for teachers, a classroom simulation of the science AR application, and intensive mentoring during the teaching and learning process. To overcome infrastructure and network constraints in the 3T region, the AR application was designed to be fully accessible offline. The program's success was evaluated using pre-test and post-test instruments measuring science literacy skills, alongside student response questionnaires. Results: The results demonstrated a significant increase in students' science literacy achievements, particularly in understanding abstract natural concepts. The use of AR media successfully boosted student enthusiasm, motivation, and active engagement in classroom learning, reaching a